5 - Multiple meanings of the middle class in Soweto, South Africa - Claire Ceruti,; Mosa Phadi, (African Sociological Review, 2011)
This study investigated the meanings of middle class amongst those who label themselves middleclass. 2559 people were surveyed in Soweto, South Africa biggest township. The study revealed that a diverse number of people call themselves middle class and defined class in terms of ability to afford basic goods. The label middle class seems also to denote self-sufficiency, responsibility and social mobility The paper concludes that studies of the middle class does not seen to focus on how social location affects the scope of people’s social world and their range of comparison.